2006
DOI: 10.1016/j.bbamcr.2006.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial membrane dynamics, cristae remodelling and apoptosis

Abstract: Mitochondria form a highly dynamic reticular network in living cells, and undergo continuous fusion/fission events and changes in ultrastructural architecture. Although significant progress has been made in elucidating the molecular events underlying these processes, their relevance to normal cell function remains largely unexplored. Emerging evidence, however, suggests an important role for mitochondrial dynamics in cellular apoptosis. The mitochondria is at the core of the intrinsic apoptosis pathway, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 178 publications
4
68
0
Order By: Relevance
“…Mitochondrial fragmentation, as a result of altered morphological dynamics, has been implicated in mitochondrial injury during apoptosis (11)(12)(13)(14). Our results now further suggest that the mitochondrial fragmentation may involve Bak.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Mitochondrial fragmentation, as a result of altered morphological dynamics, has been implicated in mitochondrial injury during apoptosis (11)(12)(13)(14). Our results now further suggest that the mitochondrial fragmentation may involve Bak.…”
Section: Discussionsupporting
confidence: 69%
“…Recent studies have revealed a striking morphological change of mitochondria during apoptosis (11)(12)(13)(14). Upon apoptotic stimulation, mitochondria collapse from a filamentous network into punctate fragments.…”
mentioning
confidence: 99%
“…The OMM surrounds an IMM which encloses a protein-rich matrix containing the mitochondrial DNA. The large surface area of the IMM in relation to that of the OMM necessitates organization of the IMM into numerous invaginations, or cristae (63,64). Mammalian cells maintain the overall shape of their mitochondria by balancing the opposing processes of mitochondrial fusion and fission (1,7).…”
Section: Mitochondrial Morphology Dynamicsmentioning
confidence: 99%
“…37,38 It should be noted, however, that mitochondrial morphology is dynamic and mitochondrial fragmentation precedes apoptosis in several systems. 39,40 As LSD cells are more sensitive to apoptosis, 18 the possibility remains that mitochondrial fragmentation in our system reflects pre-apoptotic changes.…”
Section: Introductionmentioning
confidence: 99%